2024
DOI: 10.3390/ijms25042214
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipocalin-2 Levels as a Biomarker in Pre- and Post-Pubertal Klinefelter Syndrome Patients: A Pilot Study

Roberto Paparella,
Giampiero Ferraguti,
Marco Fiore
et al.

Abstract: Klinefelter syndrome (KS) is a male genetic disease caused by the presence of an extra X chromosome, causing endocrine disorders mainly responsible for a high rate of infertility and metabolic disorders in adulthood. Scientific research is interested in identifying new biomarkers that can be predictive or prognostic of alterations strictly connected to KS. Lipocalin-2 (LCN-2, also known as NGAL) is a small protein initially identified within neutrophils as a protein related to innate immunity. Serum LCN-2 esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Follow-up studies revealed increased psychiatric referrals and diagnoses, notably depression, among XXY individuals compared to controls [15,42]. Emotional arousal difficulties and challenges in emotional expression were noted, potentially contributing to the under-reporting of psychiatric symptoms in KS [23,[43][44][45][46][47][48][49][50]. Psychiatric screenings among the KS population showed elevated rates of psychosis and depression [40,51].…”
Section: Emotional Problemsmentioning
confidence: 98%
“…Follow-up studies revealed increased psychiatric referrals and diagnoses, notably depression, among XXY individuals compared to controls [15,42]. Emotional arousal difficulties and challenges in emotional expression were noted, potentially contributing to the under-reporting of psychiatric symptoms in KS [23,[43][44][45][46][47][48][49][50]. Psychiatric screenings among the KS population showed elevated rates of psychosis and depression [40,51].…”
Section: Emotional Problemsmentioning
confidence: 98%